DINAMIKA POLITIK DAN PILKADA DI KOTA KENDARI: Analisis Pengaruh Media Sosial dalam Kampanye Politik Lokal - Yunita Simatupang (Halu Oleo University, 2024)
This study aims to analyze the role and impact of social media in political contestation leading up to the gubernatorial election in Southeast Sulawesi, utilizing the public sphere theory developed by Jurgen Habermas. The findings indicate that social media plays a significant role in enhancing political participation, particularly among younger, more tech-savvy voters. However, the study also identifies serious challenges related to the spread of misinformation and hoaxes, which can manipulate public perception and undermine the integrity of the democratic process. Therefore, it is crucial for candidates and their campaign teams to develop effective strategies to counter misinformation, and for the government and relevant institutions to enforce strict regulations on social media content during the campaign period. The conclusion of this study is that while social media holds great potential to strengthen democracy by increasing transparency and participation, its misuse can pose serious threats to political and social stability. Hence, appropriate strategies and strong digital literacy are necessary to harness social media as an effective tool in supporting a healthy and sustainable democracy in Indonesia.